Los vestigios industriales: estudio, conservación y uso - Benito del Pozo, Carmen (Estudios humanísticos. Geografía, historia y arte, 1998)
Conservation of industrial heritage as a cultural item has allowed the consolidation of a new discipline called Industrial Archaeology, focused on the study, catalogation and conservation of material remains linked to the process of industrialization which emerged from English revolution in late 18th century. The article analyzes the principles on which Community cultural policy is based, as well as the means of finance offered by European institutions to help projects of cultural heritage conservation. Finally, it describes the proceedings which are being carried out in Asturias regarding conservation and studies of industrial heritage.